Comparison of the impact of autologous cell therapy and conservative standard treatment on tissue oxygen supply and course of the diabetic foot in patients with chronic limb-threatening ischemia: A randomized controlled trial - Dubský, Michal; Husáková, Jitka; Bem, Robert; Jirkovská, Alexandra; Němcová, Andrea; Fejfarová, Vladimíra; Sutoris, Karol; Kahle, Michal; Jude, Edward B. (Frontiers in Endocrinology, 2022)
Background: Autologous cell therapy (ACT) is a new treatment method for patients with diabetes and no-option chronic limb-threatening ischemia (NO-CLTI). We aimed to assess the impact of ACT on NO-CLTI in comparison with standard treatment (ST) in a randomized controlled trial. Methods: Diabetic patients with NO-CLTI were randomized to receive either ACT (n=21) or ST (n=19). After 12 weeks, those in the ST group, who did not improve were treated with ACT. The effect of ACT on ischemia and wound healing was assessed by changes in transcutaneous oxygen pressure (TcPO2) and the number of healed patients at 12 weeks. Pain was evaluated by Visual Analogue Scale (VAS). Amputation rates and amputation-free survival (AFS) were assessed in both groups. Results: During the first 12 weeks, TcPO2 increased in the ACT group from 20.8 ± 9.6 to 41.9±18.3 mm Hg (p=0.005) whereas there was no change in the ST group (from 21.2 ± 11.4 to 23.9±13.5 mm Hg). Difference in TcPO2 in the ACT group compared to ST group was 21.1 mm Hg (p=0.034) after 12 weeks. In the period from week 12 to week 24, when ST group received ACT, the TcPO2 in this group increased from 20.1±13.9 to 41.9±14.8 (p=0.005) while it did not change significantly in the ACT in this period. At 24 weeks, there was no significant difference in mean TcPO2 between the two groups. Wound healing was greater at 12 weeks in the ACT group compared to the ST group (5/16 vs. 0/13, p=0.048). Pain measured using VAS was reduced in the ACT group after 12 weeks compared to the baseline, and the difference in scores was again significant (p<0.001), but not in the ST group. There was no difference in rates of major amputation and AFS between ACT and ST groups at 12 weeks. Conclusions: This study has showed that ACT treatment in patients with no-option CLTI and diabetic foot significantly improved limb ischemia and wound healing after 12 weeks compared to conservative standard therapy. Larger randomized controlled trials are needed to study the benefits of ACT in patients with NO-CLTI and diabetic foot disease.